KOMPLEKSITAS PROSES PENGAMBILAN KEPUTUSAN DALAM ORGANISASI: STUDI PADA UKKPK DI UNIVERSITAS NEGERI PADANG - Iqra' Syahadatul Aisyah; Syamsir, Syamsir; Andini, Amalia; Salsabilla, Salsabilla; Ratu Gustia Fernanda; Septina Angraini; Widya Junita Putri; Yulianda Flora (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the complexity of the decision-making process within the Student Communication and Broadcasting Organization (UKKPK) at Universitas Negeri Padang. Decision making in student organizations is an important aspect because it is closely related to the implementation of work programs, organizational coordination, and the achievement of organizational goals. This study employed a qualitative descriptive approach. Data were collected through interviews, observations, and documentation involving the Head of UKKPK, members of the Daily Executive Board (DPH), and organizational members as informants. The results showed that the decision-making process in UKKPK was carried out systematically through DPH meetings, work program planning, committee formation, member discussions, and organizational general meetings. The decision-making process was participatory by involving administrators, members, and organizational alumni. However, several obstacles were still encountered, such as limited time, differences in members' schedules, and insufficient information that could affect the effectiveness of organizational decisions. To overcome these challenges, the organization conducted further discussions, utilized senior members' experiences, and implemented a voting mechanism when differences of opinion occurred within organizational forums. Decision making within UKKPK is not only oriented toward organizational rationality, but also emphasizes deliberation, group communication, and member participation in achieving organizational goals effectively and democratically.